Community Based Management Of Sustainable Mangrove Ecosystems In Kendari City, Southeast Sulawesi - Walid Walyudin Rahman; Achmad Husen; Ananto Kusuma Seta (Eduvest - Journal of Universal Studies, 2024)
Mangrove ecosystems are a form of important role in maintaining the stability of the coastal environment that has ecological, physical and economic-social functions so as to provide interaction between people who live in mangrove areas. efforts in managing sustainable mangrove ecosystems in order to provide carrying capacity to all parties so as to identify, analyze, determine the needs and potential of natural resources in mangrove ecosystems. Mangrove ecosystem damage is caused by two things, namely community activities and natural factors so as to prevent degradation, the application of sustainable mangrove ecosystem management is carried out optimally to preserve mangroves. The study aims to determine the observation of ecosystems and community concepts in sustainable mangrove management in Kendari City. This research method uses descriptive quantitative with sampling techniques using cluster sampling and direct observation data collection. The results of this study indicate that the results of observations from two areas in Kendari City, namely mangroves in the Nambo area with observations of natural / bio and physical environment score range 23 is quite fulfilling for mangrove management while mangroves in the Bungkutoko area score range 37 is very fulfilling said to be sustainable for mangrove management and the results of the questionnaire statement regarding the concept of management descriptively shows community-based sustainable ecosystem management strongly agrees to be well implemented and can be said to be sustainable in mangrove ecosystem management Kendari City Southeast Sulawesi.